2016
DOI: 10.1016/j.micinf.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The salivary microbiome for differentiating individuals: proof of principle

Abstract: Human identification has played a prominent role in forensic science for the past two decades. Identification based on unique genetic traits is driving the field. However, this may have limitations, for instance, for twins. Moreover, high-throughput sequencing techniques are now available and may provide a high amount of data likely useful in forensic science.This study investigates the potential for bacteria found in the salivary microbiome to be used to differentiate individuals. Two different targets (16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 28 publications
0
60
0
1
Order By: Relevance
“…However, most of the studies on this topic have employed pooled salivas or individual salivas from a limited number of subjects (Buettner, 2002a(Buettner, , 2002bGenovese et al, 2009;Munoz-Gonzalez et al, 2018b;Munoz-Gonzalez et al, 2014;Pages-Helary et al, 2014) that do not represent properly the well-known interindividual variability of human saliva composition in healthy individuals (Leake, Pagni, Falquet, Taroni, & Greub, 2016;Neyraud, Palicki, Schwartz, Nicklaus, & Feron, 2012). Additionally, different pathologies or functional states can provoke biochemical and microbiological changes in salivary parameters raising the differences in specific populations (Castagnola, Cabras, Vitali, Sanna, & Messana, 2011;Schipper, Silletti, & Vinyerhoeds, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies on this topic have employed pooled salivas or individual salivas from a limited number of subjects (Buettner, 2002a(Buettner, , 2002bGenovese et al, 2009;Munoz-Gonzalez et al, 2018b;Munoz-Gonzalez et al, 2014;Pages-Helary et al, 2014) that do not represent properly the well-known interindividual variability of human saliva composition in healthy individuals (Leake, Pagni, Falquet, Taroni, & Greub, 2016;Neyraud, Palicki, Schwartz, Nicklaus, & Feron, 2012). Additionally, different pathologies or functional states can provoke biochemical and microbiological changes in salivary parameters raising the differences in specific populations (Castagnola, Cabras, Vitali, Sanna, & Messana, 2011;Schipper, Silletti, & Vinyerhoeds, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The salivary microbiomes can be characterized by a significantly lower interindividual variability than microbial communities of other body sites such as the gut, 7 , 8 but it is possible to differentiate individuals by phylogenic approaches 9 . Though the salivary microbiome is associated with gut microbiome, 10 , 11 the diversity in salivary microbiomes showed relatively low associations with several affecting factors including long-term diet, 12 weight and gender, 13 geographic location, 14 and antibiotic treatment (high tolerance) 15 compared with that of the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Researches have demonstrated the potential to identify a single individual in large populations, based on microbial fingerprints from metagenomic tags, even over long periods of time [42,55]. It has also been shown that skin bacterial profiles can be confidently used to link specific individuals to objects touched, even after months [56], provided the objects have since remained untouched [31].…”
Section: Identitymentioning
confidence: 99%